Hazards analysis of LPG storage installation in Universiti Putra Malaysia: A preliminary study - Mohanad, El-Harbawi; Sa’ari, M.; Choong, Thomas Shean Yaw, Assoc. Prof. Dr.; Chuah, T. G.; Abdul Rashid, M. S. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/